2013
DOI: 10.1177/1477370812471247
|View full text |Cite
|
Sign up to set email alerts
|

Prison-based drug treatment in Nordic political discourse: An elastic discursive construct

Abstract: Prison-based drug treatment (PDT) has increased markedly in the Nordic countries over the last 15 years. Based on data from Denmark, Finland, Norway and Sweden, we outline the historical development of PDT and analyse the rationales employed in the political discourse in the Nordic countries legitimizing this development. These rationales relate to the reduction of criminality, zero tolerance, rights and the modern welfare state, and managerialism. Though these rationales may appear dissimilar, they have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
1
27
0
2
Order By: Relevance
“…First, the article offers a study of drug use in the context of prison-based drug rehabilitation. There has been a rapid increase in prison-based drug rehabilitation in the Nordic countries the last 15 years (Kolind, Frank, Lindberg, & Tourunen, 2013), and research has shown that prison-based drug rehabilitation may reduce the demand for illegal drugs in prisons (Hedrich et al, 2012;Penfold et al, 2005). The article seeks to investigate how drug use is perceived and handled by participants and staff in two different drug rehabilitation programmes in a Norwegian prison.…”
Section: Introductionmentioning
confidence: 99%
“…First, the article offers a study of drug use in the context of prison-based drug rehabilitation. There has been a rapid increase in prison-based drug rehabilitation in the Nordic countries the last 15 years (Kolind, Frank, Lindberg, & Tourunen, 2013), and research has shown that prison-based drug rehabilitation may reduce the demand for illegal drugs in prisons (Hedrich et al, 2012;Penfold et al, 2005). The article seeks to investigate how drug use is perceived and handled by participants and staff in two different drug rehabilitation programmes in a Norwegian prison.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the proportion of offenders sentenced for drug offences has increased markedly in the Nordic countries . As a consequence of these developments, the daily prison routine is in many respects dictated by drug-using inmates and drug-related problems, including a growth in drug treatment programs and in control measures aimed at preventing drug trafficking and drug-related violence (Kolind et al, 2013). Despite the fact that drug use in prison and drug-related problems have been relatively well documented, only a few studies have examined the role of drugs in the everyday life of prisons (Crewe, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ruspolitikk basert på empowerment har også vist seg å vaere utfordrende å implementere på helsefeltet (Frank og Bjerge 2011). Selv om offentlig politikk legger til grunn at innsatte rusbrukere skal møtes på en måte som gir mer autonomi, styring og kontroll over eget liv (Kolind, Frank, Lindberg og Tourunen 2013), er det forsket lite på hvordan innsatte opplever dette i praksis (Giertsen, Nylander, Frank, Kolind og Tourunen 2015;Mjåland 2015). Denne artikkelen undersøker derfor hvilke erfaringer innsatte rusbrukere ved norske rusmestringsenheter har med selv-og medbestemmelse av mål og virkemidler i behandlings-og rehabiliteringsprosesser.…”
unclassified